The Brill Knowledge Graph: A Database of Bibliographic References and Index Terms Extracted from Books in Humanities and Social Sciences (Research Data Journal for the Humanities and Social Sciences, 2024)
With the recognition of content discoverability and information analytics in the  scientific publishing industry, more and more effort is dedicated to digitization  and automated analysis of scholarly publications. As part of this effort, the authors  research data journal for the humanities and social sciences 9 (2024) 1–21 designed a pipeline to extract structured information from bibliography and index lists  of existing scholarly publications, as well as to disambiguate and export it as linked  data. In this article, the authors present the Brill Knowledge Graph (kg), obtained by  applying this pipeline to a corpus of books in the Arts, Humanities and Social Sciences  (ahss) provided by the publisher Brill.